KEBERAGAMAN BUDAYA INDONESIA DAN POTENSI KONFLIK LINTAS BUDAYA: STUDI LITERATUR MENGENAI KONFLIK KEBERADAAN ETNIS TIONGHOA DI INDONESIA - Anggraeni, Diana (Jurnal Insani, 2022)
The purpose of this paper is to determine the relationship between cultural diversity and the potential for cross-cultural conflicts that occur between ethnic Chinese and ethnic Indigenous people in Indonesia. Even though they have been present in the archipelago for thousands of years, the stereotype of the presence of ethnic Chinese is still very strong, namely, with the assumption that they are immigrants who only live here looking for food. Not to mention the prejudice that says that the Chinese are not willing to blend in and tend to be exclusive coupled with the ethnocentric attitude of the indigenous ethnic that the Chinese are a minority group. This study uses a literature study, trying to explain, describe and analyze the conflicts experienced by ethnic Chinese which are collected through books, articles, research results, and relevant written sources. The results of the analysis state that the ethnic Chinese conflict with the Indigenous ethnic group has occurred for a long time. The suspicion factor is the main reason for the conflict. Ethnic Chinese are always the target if there is a conflict, even though the conflict is from another ethnic group. This shows that the existence of ethnic Chinese is still not fully accepted. Cultural diversity is a huge potential for Indonesia if managed properly. For this reason, it is necessary to have empathy, openness, tolerance, respect or differences and develop good cross-cultural communication to avoid misunderstandings.